DIETARY SUPPLEMENTATION OF VITAMIN C, L-ASCORBATE 2-TRIPHOSPHATE CALCIUM (LATP-Ca) ON OOCYTE DEVELOPMENT OF MAJOR CARP ROHU (LABEO ROHITA) REARED IN A NATURAL CONCRETE POND - Labh, Shyam Narayan (Ecoprint: An International Journal of Ecology, 2014)
The aim of this study was to evaluate the effect of vitamin C L-ascorbate 2-triphosphate (LATP-Ca)on Indian major carp rohu (Labeo rohita) (Hamilton) during intensive aquaculture. Rohu were fedwith vitamin C (LATP-Ca) supplementation at doses of D1 (control) and D2 (500 mg/kg) diet for 10weeks. The effects were assessed by comparing the treated groups of fish to that of control group.Vitamin C (LATP-Ca) supplementation exerted significant (P<0.05) effects on oocyte developmentof rohu (Labeo rohita). A number of distinct developmental stages of oocyte can be delineated andoocyte growth in major carp rohu (Labeo rohita) found in two distinct phases; primary growthphase (PGP) and the secondary growth phase (SGP). In PGP, oogonia, chromatin nucleolus, earlyand peri nucleolus stage oocyte with Balbiani’s vitelline body were observed while two types ofinclusions, lipid and protein, respectively were formed during vitellogenesis in the SGP. SGPdevelopment was found for a short period of time as compared to PGP. Similarly, development ofoocyte was very poor in fish fed with controlled diet. DOI: http://dx.doi.org/10.3126/eco.v19i0.9849 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 7-15 Uploaded date: 2/14/2014